2020
DOI: 10.3390/ijms21062045
|View full text |Cite
|
Sign up to set email alerts
|

Abberant Immunoglobulin G Glycosylation in Rheumatoid Arthritis by LTQ-ESI-MS

Abstract: Aberrant glycosylation has been observed in many autoimmune diseases. For example, aberrant glycosylation of immunoglobulin G (IgG) has been implicated in rheumatoid arthritis (RA) pathogenesis. The aim of this study is to investigate IgG glycosylation and whether there is an association with rheumatoid factor levels in the serum of RA patients. We detected permethylated N-glycans of the IgG obtained in serum from 44 RA patients and 30 healthy controls using linear ion-trap electrospray ionization mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…IgG1 and IgG2 sialylation also decreased in GPA, as confirmed by liquid chromatography coupled with mass spectrometry 57 . Su et al observed a negative correlation between the serum levels of total sialylated IgG and RF autoantibodies in RA patients, suggesting that sialylation levels may be promising serum biomarkers for RA disease activity and clinical diagnosis 59 .…”
Section: Sialylated Igg In Autoimmune Diseasesmentioning
confidence: 99%
“…IgG1 and IgG2 sialylation also decreased in GPA, as confirmed by liquid chromatography coupled with mass spectrometry 57 . Su et al observed a negative correlation between the serum levels of total sialylated IgG and RF autoantibodies in RA patients, suggesting that sialylation levels may be promising serum biomarkers for RA disease activity and clinical diagnosis 59 .…”
Section: Sialylated Igg In Autoimmune Diseasesmentioning
confidence: 99%
“…In addition to viral infections, aberrant glycosylation of antibodies has been described for several other disorders. These include a number of autoimmune diseases, such as RA [ 105 , 106 ] and MS [ 107 ]. In RA, these antibodies may promote inflammation through activation of synovial macrophages [ 32 , 34 ].…”
Section: Pathological Immune Activationmentioning
confidence: 99%
“…Their study showed that total purified IgG from RA has considerably lower galactosylation, lower sialylation, and higher fucosylation compared to that in healthy controls. Hence, in RA patients there should be a positive association between aberrant N-glycosylation and RF levels [ 93 ]. Recently, analysis of crystal structures of ACPA demonstrated that the V-domain glycans are positioned in the vicinity of the binding-pocket.…”
Section: The Role Of Epigenetic Modifications and Glycosylation In Ramentioning
confidence: 99%
“…Their dynamic modeling has shown the potential of V-domain glycans to interact with the antigen-binding regions. It is noteworthy that human Ramos B-cells carrying V-domain glycosylated B-cell receptors (compared to their non-glycosylated counterparts) undergo increased signaling after stimulation [ 93 ]. Furthermore, glycan-based nanoparticles recently have been used to boost the immune system [ 94 ].…”
Section: The Role Of Epigenetic Modifications and Glycosylation In Ramentioning
confidence: 99%